let A=(3 x)

(-2 -3)
if A=A^-1, what is x?

please show work so i can understand

Is (3 x) a 2 x 1 matrix?

What is the meaning of the second line, (-2 -3)? It just sits there.

Is the A matrix in the first line supposed to operate on (3 x) ?

(3 x) and (-2 -3) cannot be multiplied.
One has ti be a column vector.

The second line is probably meant to be the second row of the 2x2 matrix.

I.e. A=
(3 x}
(-2 -3)

If A=A-1, then
A-1A = I

(3 x} (3 x}
(-2 -3)(-2 -3) = I

Performing the matrix multiplication:
(9-2x 0)
(0 -2x+9) = I

so
9-2x=1
or x=4

Substitute x=4 and redo the matrix multiplication to make sure that the result is a 2x2 identity matrix.

To find the inverse of matrix A, we need to solve the equation: A * A^(-1) = I, where I is the identity matrix.

Given matrix A:
A = [ 3 x ]
[ -2 -3 ]

We need to find its inverse A^(-1) such that A * A^(-1) = I.

Let's calculate the product of A and A^(-1) first:
A * A^(-1) = [ 3 x ] * [ a b ] = [ 1 0 ]
[ -2 -3 ] [ c d ] [ 0 1 ]

Using matrix multiplication, we get the following equations:
3a - 2c = 1 ...(1)
3b - 2d = 0 ...(2)
-xa - 3c = 0 ...(3)
-xb - 3d = 1 ...(4)

Let's solve these equations simultaneously to find the values of a, b, c, and d which represents the inverse matrix.

From equation (1), we can determine a in terms of c:
3a = 1 + 2c
a = (1 + 2c)/3 ...(5)

From equation (2), we can determine b in terms of d:
3b = 2d
b = 2d/3 ...(6)

Substituting equations (5) and (6) into equations (3) and (4), we get:
-x((1 + 2c)/3) - 3c = 0 ...(7)
-x(2d/3) - 3d = 1 ...(8)

Let's solve equations (7) and (8) for x:

From equation (7), we can solve for c in terms of x:
-((1 + 2c)/3) = 3cx
-1 - 2c = 9cx
c(-2 - 9x) = -1
c = -1/(-2 - 9x)
c = 1/(2 + 9x) ...(9)

Substituting equation (9) into equation (8), we can solve for d in terms of x:
-x(2d/3) - 3d = 1
-x(2d)/3 - 3d = 1
(-2x/3 - 3)d = 1
d = 1/(-2x/3 - 3)
d = -3/(2x + 9) ...(10)

Now that we have expressions for c and d in terms of x, we can substitute these values into equations (5) and (6) to obtain expressions for a and b:

a = (1 + 2c)/3
a = (1 + 2(1/(2 + 9x)))/3
a = (1 + 2/(2 + 9x))/3
a = (2 + 2/(2 + 9x))/3
a = (2(2 + 9x) + 2)/(3(2 + 9x))
a = (4 + 18x + 2)/(6 + 27x)
a = (18x + 6)/(6 + 27x) ...(11)

b = 2d/3
b = 2(-3)/(3(2x + 9))
b = -6/(6 + 27x) ...(12)

Finally, we set x = a, since A = A^(-1). From equation (11), we have:

a = (18a + 6)/(6 + 27a)

Now, we can solve for a:

6a + 27a^2 = 18a + 6
27a^2 - 12a = 0
3a(9a - 4) = 0

This equation will have two solutions:
a = 0 (discard this solution because it will not yield an inverse matrix)
9a - 4 = 0
9a = 4
a = 4/9

Therefore, x = a = 4/9.